Progress in fatigue life calculation by implementing life-dependent material parameters in multiaxial fatigue criteria. (May 2020) - Karolczuk, Aleksander; Papuga, Jan; Palin-Luc, Thierry
Highlights: Results of new fatigue tests on 2024-T851 aluminium alloy are presented. The concept of life-dependent material parameters is presented. This concept has been successfully applied to the stress-based criteria. The assessed fatigue lives are better on the AL-2024-T851 when using this concept. Abstract: This paper presents the concept of applying life-dependent material parameters to several multiaxial fatigue criteria. This concept reflects the transformation of damage mechanisms in relation to the applied load level, and also in relation to the varying level of plasticity. The goal of this study is to demonstrate the benefit of introducing life-dependent material parameters into stress-based multiaxial fatigue criteria for predicting the fatigue life of materials. New experimental results of fatigue tests on 2124-T851 aluminium alloy confirm the advantage of the life-dependent concept in life assessment over the concept with fixed weight parameters.